Systemic Functional Linguistics: Meaning Carriers In Functional Grammar - Ferry Adenan (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2001)
Emeritus Professor M.A.K Halliday, founding Professor of Linguistics at the University of Sydney, Australia, is often regarded as the linguist responsible for the development of systemic functional linguistics. Systemic functional linguistics is a comprehensive descriptive model of language and language use which has been evolving for many years. It is still evolving as applied linguists continue to research and reflect on the way human beings use language to make meaning in social contexts. Educators and linguists are both concerned with SFL. Educators would like to know how people learning the language can follow native speakers of the language to use the language. Therefore, SFL is to build a discipline of educational linguistics. In practice educational linguistics may mean, “learning language, learning through language, learning about language”, (Cope, B. et. Al. 1993). Educational linguistics brings linguists and educators together to deepen their insight about language and language use and to easen their professional duties. SFL is ‘systemic’ because whenever a feature of language is described it is described as one choice from a set of possible choices within a particular language system which itself is part of a network of systems that make up the language. The systems are related in a kind of hierarchy making it possible to describe an aspect of language at whatever level of detail is the most useful. Language users are constantly making choices from the set of systems which make up the complete resource of language and then putting these choices into effect through the structure of the language they use. Understanding this process can provide very useful insight for language teachers and users.